On the foaming properties of plant proteins: Current status and future opportunities - Amagliani, Luca; Silva, Juliana V.C.; Saffon, Maxime; Dombrowski, Jannika (Trends in food science & technology, 2021)
Aerated food products are becoming increasingly popular among consumers due to their visual appeal and peculiar sensory properties. Foam formation and stabilization are typically achieved using clean label surface-active molecules such as proteins. In recent years, the need to address pressing global challenges like food security and sustainability has steered the attention of food companies towards the replacement of animal proteins with plant-based ones. This trend has promoted the development and commercialization of a variety of plant protein-enriched ingredients that differ widely in their techno-functionality. The aim of this study was to provide a review of the foaming properties of selected plant proteins and to describe how these are influenced by the extraction processes as well as by physical, chemical and enzymatic treatments. The characterization of the foaming properties of plant proteins has been the subject of extensive research over the past couple of decades. However, drawing general conclusions based on the outcomes of different studies is a complex endeavor, even for protein ingredients derived from the same plant species. This is not only due to differences in terms of cultivars, environmental factors, farming practices and extraction processes, but also in the methods and conditions used to generate and analyze foams. Nevertheless, this review highlights the potential of different approaches to improve the foaming properties of plant proteins, including the optimization of extraction conditions, the use of physical, chemical and enzymatic treatments, and the modulation of their interactions with other food components. •Foaming properties of plant proteins have been extensively investigated in recent years.•A review of the foaming properties of selected plant proteins is provided.•Differences in cultivars and extraction processes complicate comparison between studies.•Foaming performance is closely related to the protein profile of the protein source.•The influence of physical, chemical and enzymatic treatments on foaming is described.